Study on the evolving role of the People’s Republic of China in resolving the conflict in the Islamic Republic of Afghanistan - F. F. Sharipov; М. A. Dyakonova (Управление)
The age-old struggle for influence in Asia, intensified in recent decades, has gained a new player in the form of dynamic China, one of the leaders of world politics and the economy of today. The authors draw on the opinions of foreign and domestic experts to determine the reasons for the involvement and role of the People’s Republic of China (PRC) in resolving the conflict in the Islamic Republic of Afghanistan (IRA) and to link these activities to China’s renewed strategy in the Middle East as a whole. The research done by the authors over the last six months has developed rapidly in recent weeks and even days, indicating that geopolitical turbulence is developing in recent times.The article classifies the full range of the People’s Republic of China interests in the Islamic Republic of Afghanistan and identifies the factors that influence the formation of China’s system of interests in Afghanistan, including factors in the international environment. The consequences of the pandemic and China’s new opportunities to use soft power to advance its interests have been identified. The People’s Republic of China’s strategy in the region has been defined and attention has been paid to security issues.Beijing’s envisaged steps to promote its projects in the region have been presented.